Candidate genes for limiting cholestatic intestinal injury identified by gene expression profiling. Issue 4 (17th September 2013) - Alaish, Samuel M.; Timmons, Jennifer; Smith, Alexis; Buzza, Marguerite S.; Murphy, Ebony; Zhao, Aiping; Sun, Yezhou; Turner, Douglas J.; Shea‐Donahue, Terez; Antalis, Toni M.; Cross, Alan; Dorsey, Susan G.
Abstract The lack of bile flow from the liver into the intestine can have devastating complications including hepatic failure, sepsis, and even death. This pathologic condition known as cholestasis can result from etiologies as diverse as total parenteral nutrition (TPN), hepatitis, and pancreatic cancer. The intestinal injury associated with cholestasis has been shown to result in decreased intestinal resistance, increased bacterial translocation, and increased endotoxemia. Anecdotal clinical evidence suggests a genetic predisposition to exaggerated injury. Recent animal research on two different strains of inbred mice demonstrating different rates of bacterial translocation with different mortality rates supports this premise. In this study, a microarray analysis of intestinal tissue following common bile duct ligation (CBDL) performed under general anesthesia on these same two strains of inbred mice was done with the goal of identifying the potential molecular mechanistic pathways responsible. Over 500 genes were increased more than 2.0‐fold following CBDL. The most promising candidate genes included major urinary proteins (MUPs), serine protease‐1‐inhibitor (Serpina1a), and lipocalin‐2 (LCN‐2). Quantitative polymerase chain reaction (qPCR) validated the microarray results for these candidate genes. In an in vitro experiment using differentiated intestinal epithelial cells, inhibition of MUP‐1 by siRNA resulted in increased intestinal epithelial cell permeability. Diverse novel mechanisms involving the growth hormone pathway, the acute phase response, and the innate immune response are thus potential avenues for limiting cholestatic intestinal injury. Changes in gene expression were at times found to be not only due to the CBDL but also due to the murine strain. Should further studies in cholestatic patients demonstrate interindividual variability similar to what we have shown in mice, then a "personalized medicine" approach to cholestatic patients may become possible.